EFL teachers’ digital literacy: the role of contextual factors in their literacy development - Zhang, Jie (Frontiers in Psychology, 2023)
Introduction Digital technology can have significant effects on language education. This effect makes the English language teachers teach the subjects better to the students and also improves the quality of teachers’ education. Methods The purpose of this research is to evaluate the digital literacy of English language teachers and to investigate the difference between digital literacy and their gender, education level, and teaching experience. To conduct the study, the researcher invited 2,110 EFL teachers to fill out the Teachers’ Digital Literacy questionnaire. The researchers used SPPS and AMOS in analyzing the obtained data. Results The results of the study indicated that teachers’ contextual factors do not influence their digital literacy skills. In addition, the study showed that teachers’ attitudes toward technology, their skill to use technology, and their access to technology can significantly affect teachers’ digital literacy. Discussion Implications of the study are further discussed in this paper.